Improve Social and Academic Innovation Through Governance Reform - Darian Dexter (International Journal of Science and Society, 2022)
Governance Reform for Economic and Social Progress. Recent years have seen an increase in the number of research concentrating on interactive forms of governance, perhaps as a response to the growth of governance networks across all levels and policy domains. This study is an effort to further the field of governance studies by investigating the potential of governance networks to promote social and pedagogical advancements through collaboration. The study begins by outlining what governance networks are and then moves on to systematically reviewing the various ideas that attempt to account for their recent proliferation. Next, it offers a working definition of innovation and explores the ways in which networked cooperation fosters creative output. Finally, it explains how novel approaches to leadership and management can spark, foster, and catalyze collaborative innovation. Reform in the Classroom.